Can ‘tourism product development’ compensate the social cost of carbon pollution? A case study in Sri Lanka - Rathnayake, Wasantha; Rajapakshe, Himani (Interdisciplinary Research Review, 2018)
The study examines how tourism product development can help generate sufficient revenue for park management to offset the social cost of carbon pollution associated with tourism product development. The results show that the social cost incurred at present due to observing wildlife at Wasgomuwa National Park (WNP) is Sri Lanka Rupees (SLR) 1.88 million (12912.56 USD) and the mean social cost per person is SLR 94.93 (0.65 USD) though only SLR 60.00 is recovered as the park entrance fee. If the existing park entrance fee is used for a carbon minimizing environmental conservation programme, the net loss per visitor would be SLR 34.93. However, if the mean WTP values are considered as the park entrance fee, the per person contribution for compensating the social cost of carbon pollution will be SLR 67.52 and SLR 82.66, respectively, under the recreational schemes 1 and 2. This saving can be utilized to offset the social cost of carbon pollution.